DINÂMICA DE ATUAÇÃO DO CONSELHO MUNICIPAL DE SAÚDE DE SANTA MARIA - RS: CIDADANIA E CONTROLE SOCIAL EM PAUTA - Favarini, Daniele Cristiane Silva Rodrigues (2021)
The Municipal Health Councils are collegiate instances of social participation organized in the co-management of the Unified Health System - SUS. They are formed by representations of users, health professionals, health service providers and government representatives, who act as advisers. The counselor's role involves some factors that directly affect the process of consolidation and strengthening of these democratic spaces. Considering the above, this study has the following research question: how is the performance in the Municipal Health Council, considering the exercise of citizenship and social control, according to the vision of the councilors? Therefore, the objective of the study is to know the dynamics of action of counselors in the Municipal Health Council of Santa Maria - RS, with a view to exercising citizenship and the visibility of this instance of social control in the community. This is an exploratory-descriptive research with a qualitative approach. The study was carried out at the Municipal Health Council of Santa Maria, Rio Grande do Sul. The study included 14 councilors, 7 of which represented the segment of users and the other 7 the other representations. The study was carried out from August 2020 to June 2021. The technique for data collection was the semi-structured interview, which was carried out via digital platforms, due to the Covid-19 pandemic. Data were analyzed according to thematic content analysis, which was operationally organized into three stages: pre-analysis; exploration of the material; treatment of the results obtained and interpretation. Codes were used to refer to the study participants, defining the letter 'C', initial for counselor, followed by a corresponding number that ranged from 1 to 14. For this study, the ethical aspects were observed, as per Resolution no. 466/2012, of the National Research Council. The project was approved by the Research Ethics Committee, being registered according to approval no. 4,594,892. The data analysis process showed that the Board's dynamics of action corresponds to a set of responsibilities, challenges and possibilities for effective social control. Responsibilities are predominantly linked to the exercise of citizenship, the monitoring of actions and resources used in health, the role of interlocutor between the demands of the community and the defense of the SUS. The challenges remain: effective communication with the community, the low visibility of the Councils with the population and the threats to the health system, accentuated by the economic crisis and the Covid-19 pandemic. As possibilities, the strengthening of local councils, the expansion of communication channels with society and continuing education in health emerged as a way to qualify social control. The dynamics of action of counselors is a complex activity that contributes to citizenship and social control in health. This action is directly influenced by social demands and by the Brazilian socio-economic scenario and, in this sense, it needs a purposeful, not essentially supervisory, posture in the field of health policies. Despite recognized advances, this dynamic needs to achieve greater clarity of their roles in society and education processes may be able to qualify this performance.